Receptive and Expressive Language in Hindi Speaking Children with Postcochlear Implantation at 6-Month Intervals - Kumar,Vijay (2021)
Abstract Introduction Individual variability in the language outcomes of children with cochlear implantation (CI) is a major concern. In CI rehabilitation, there is lack of a protocol regarding uniform post-CI language assessment interval duration, which can ensure better understanding of the trajectory of language growth as well as optimize language outcomes by providing feedback in fine tuning the language intervention program. Objective To evaluate the receptive and expressive language in Hindi speaking children with up to 2 years of CI experience using revised receptive-expressive emergent language test-3ed. (REELT-3) at 6 months intervals and to compare it with that of children with normal hearing (NH). Methods The present study included 192 children divided in 2 groups, 96 children with CI (15.8 ± 6.7 months), and 96 age-matched children with NH (22.3 ± 7.9 months). A cross-sectional, prospective study design was used to measure the language ability score (LAS) at an interval of 6 months from the time of implantation (TIA), which is 0 to 6 months, 7 to 12 months, 13 to 18 months, and 19 to 24 months of CI usage. Results The two-way analysis of variance revealed that the LAS after 18 months of CI usage was similar to (F (3, 92) = 8.63, p= 0.19, ηp2 = 0.028) that of the children with NH. However, other demographic factors, for instance, gender (F (3, 92) = 1.73, p= 0.505, ηp2 = 0.002), parent's education, (F (3, 92) = 2.05, p= 0.937, ηp2 = 0.031), and financial background (F (3, 92) = 2.49, p= 0.351, ηp2 = 0.076) had no major impact on language. Conclusion Eighteen months of CI usage duration can potentially stimulate receptive and expressive language up to age-matched children with NH. A protocol of periodic assessment of language, at least of 6 months, may be developed to optimize language outcomes.